Ranking Work-Family Policies across OECD Countries: Implications for Work-Family Conflict, Gender Equality, and Child Well-being - I-Hsuan Lin (Social Work and Society, 2018)
This research comparatively ranks OECD countries' statutory policies of leave, early childhood education and care (ECEC), and flexible work arrangement, in terms of their levels of supportiveness and gender equality based on the Supportiveness and Gender Equality Indices. Among 33 countries, Sweden ranks 1st based on both Indices, while the United States ranks 30th for Supportiveness and 29th for Gender Equality. Mexico, Switzerland, and Turkey rank last for both Indices. Four types of policy regimes are identified. Among them, state-oriented caring regimes that challenge gendered opposition of paid work and unpaid care work through policy provisions are more likely to address work-family conflict, promote gender equality, and enhance child well-being. To better support working parents, leave would best be well paid and equally shared between fathers and mothers motivated by incentives; an entitlement to ECEC and flexibility has to be granted before or at the end of well-paid leave.